Diagnostic Value of Delayed PET/MR in Liver Metastasis in Comparison With PET/CT - Zhou, Nina; Meng, Xiangxi; Zhang, Yan; Yu, Boqi; Yuan, Jianmin; Yu, Jiangyuan; Zhu, Hua; Yang, Zhi (Frontiers in Oncology, 2021)
Objectives The aim of this study was to evaluate the value of a delayed positron emission tomography/magnetic resonance (PET/MR) scan relative to a single positron emission tomography/computed tomography (PET/CT) scan for liver metastasis detection. Methods In this study, 70 patients with solid malignancies and suspicious liver lesions undergoing 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) PET/CT and subsequent delayed liver PET/MR scans were analyzed. The histopathological analysis and/or imaging follow-up were performed as the standard of reference. Lesion maximum standardized uptake value (SUVmax), diameter, and tumor to nontumor ratio (T/N) were measured. Lesion detection sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated for both examinations. Results (1) The standard of reference revealed 208 liver lesions in 70 patients (metastasis in 56 patients with 196 lesions; benign in 14 patients with 12 lesions). Compared to PET/CT, PET/MR had higher accuracy (98.6% vs. 78.6%), sensitivity (98.2% vs. 76.8%) and specificity (100.0% vs. 85.7%). (2) The therapeutic strategies of 29 patients (41.4%) needed reconsideration after the additional PET/MR, including new metastases detected (13/70), new affected lobes identified (14/70) and false-positive corrected (2/70). (3) PET/MR detected significantly more metastases than PET/CT did, especially with small lesions. The SUVmax of the same lesion correlated well between the two acquisitions, while the delayed PET showed a higher T/N ratio. Conclusions In liver metastasis detection, the diagnostic value of the delayed PET/MR is validated to be superior to that of PET/CT, which may aid the clinical decision-making.